Tradições discursivas: a circularidade das vozes na farsa da boa preguiça - Farias, Jailine Mayara Sousa de (2012)
The present research aims at examining, on the basis of Ariano Suassuna s work Farsa da boa preguiça, in which ways the discourse traditions move through the voice and are recreated according to the cultural context in which they are in, pointing to how historical changes happen along with the cultural traditions. Therefore, the textual production is modeled according to textual traditions enclosed in each community collection of memory and imaginary, which revels the synchronic and diachronic dynamics of the discourse traditions. It is verified that Farsa da boa preguiça is permeated by memories and texts, metamorphosed to contemporary times in narrative and thematic features, underpinning variations that reflect a dynamic of continuity and rupture, in which the location of culture and the discourse traditions have a fundamental role. This work is based on diversified but complementary theoretical perspectives that deal with orality and literacy, cultural and discourse traditions, identitarian movements today, popular culture and identities. Hence, the issues proposed can be observed on the basis of many discourse features from the Northeast memory and imaginary that cuts across the utilization of genres, themes, characters, that allow us to trace a reflection on the language practices guided by different focuses.